2021
DOI: 10.1002/ange.202009518
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis Enhanced by External Fields

Abstract: The efficient conversion of solar energy by means of photocatalysis shows huge potential to relieve the ongoing energy crisis and increasing environmental pollution. However, unsatisfactory conversion efficiency still hinders its practical application. The introduction of external fields can remarkably enhance the photocatalytic performance of semiconductors from the inside out. This review focuses on recent advances in the application of diverse external fields, including microwaves, mechanical stress, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 139 publications
0
20
0
Order By: Relevance
“…Theimproved catalytic activity of BTO-90 is rationalized as follows: 1) photoexcited charge carrier separation for ferroelectric BTO employs an adjusted spontaneous internal electric field with the existence of apermanent magnetic field to generate an induced dipole;( 2) Lorentzian movement occurs for diffusion of photocatalyst and gas bubbles,r esulting in improved mass transport; [34,35] (3) the surface spin polarization of the excited photocatalyst may facilitate parallel spin alignment of chemisorbed gas atoms during the redox reaction to boost the productivity of the photocatalytic NH 3 evolution process. [6,7] To further clarify the source of NH 3 , a 15 Ni sotopic labeling experiment was performed by using 14…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…Theimproved catalytic activity of BTO-90 is rationalized as follows: 1) photoexcited charge carrier separation for ferroelectric BTO employs an adjusted spontaneous internal electric field with the existence of apermanent magnetic field to generate an induced dipole;( 2) Lorentzian movement occurs for diffusion of photocatalyst and gas bubbles,r esulting in improved mass transport; [34,35] (3) the surface spin polarization of the excited photocatalyst may facilitate parallel spin alignment of chemisorbed gas atoms during the redox reaction to boost the productivity of the photocatalytic NH 3 evolution process. [6,7] To further clarify the source of NH 3 , a 15 Ni sotopic labeling experiment was performed by using 14…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…Theimproved catalytic activity of BTO-90 is rationalized as follows: 1) photoexcited charge carrier separation for ferroelectric BTO employs an adjusted spontaneous internal electric field with the existence of apermanent magnetic field to generate an induced dipole;( 2) Lorentzian movement occurs for diffusion of photocatalyst and gas bubbles,r esulting in improved mass transport; [34,35] (3) the surface spin polarization of the excited photocatalyst may facilitate parallel spin alignment of chemisorbed gas atoms during the redox reaction to boost the productivity of the photocatalytic NH 3 evolution process. [6,7] To further clarify the source of NH 3 , a 15 Ni sotopic labeling experiment was performed by using 14 1 Hn uclear magnetic resonance (NMR) spectroscopy revealed that the Ha tom adjacent to the 14 N nuclei split into triplet peaks,w hereas 15 Ne xhibited distinguishable doublet coupling peaks (Figure 3F). Thec omparison of the above two NMR results reaffirmed that the synthetic ammonia originated completely from photocatalytic N 2 fixation.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…[12,13] Recent studies have demonstrated that an extra magnetic field could accelerate the separation of photoinduced carries effectively and there is no change for the geometries or components. [14][15][16][17] Theessence of IEF enhancement is uneven charge distribution and the generation of ad ipole.A ccording to the electronic cloud of the modified surface structure,t he induced dipole and the IEF can be effectively heightened by applicable surface defect states. However,m inimal literature data is presently available with respect to defect engineering in perovskite ferroelectric BaTiO 3 nanoparticles with spontaneous polarization;p articularly in the case of application of an external magnetic field to boost photocatalytic N 2 fixation at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The performance of ferroelectric materials can also be tuned using electrical poling. [18][19][20] Moreover, the effect of electric poling on piezocatalysis can be attributed to the ferroelectric characteristic of a noncentrosymmetric structure. On the other hand, sonocatalysis may not have any impact on poling.…”
Section: Introductionmentioning
confidence: 99%